China's Family Planning Policies and Their Labor Market Consequences - Fei Wang; Liqiu Zhao; Zhong Zhao (Institute for the Study of Labor (IZA), 2016)
China initiated its family planning policy in 1962 and one-child policy in 1980 and allows all couples to have two children as of 1st January, 2016. This paper systematically examines the labor market consequences of China's family planning policies. First, we briefly review the major historical evolution of China's family planning policies. Second, we investigate the effects of these policies on the labor market, focusing on the size and quality of the working-age population and its age and gender composition and paying special attention to regional as well as rural-urban differences in the demographic structure resulting from the interaction of the family planning policies and internal migration. Last, we discuss undergoing and prospective policy changes and potential consequences. Though urban areas and coastal provinces have implemented stricter family planning policies, our analysis shows that because of internal migration, the aging problem is more severe in rural areas and in inland provinces. Our simulation results further indicate that the new two-child policy may be too late and too little to alleviate the aging problem in China.
Keywords: J13; J11; J21; J61; 330; One-Child Policy; aging; sex ratio; quantity–quality model; migration